The Raggedy Ann stories - Gruelle, Johnny (New York : AVON BOOKS, 2011)
Raggedy Ann Stories, abreviada y adaptada del original, contiene 13 historias cortas sobre la clásica muñeca de trapo y sus amigos. El texto va acompañado de las ilustraciones originales, un glosario de imágenes y preguntas para ayudar a la comprensión. El idioma se ha simplificado para los estudiantes de inglés de alto nivel (con vocabulario en el primer nivel de 1000 palabras) y es apropiado para estudiantes jóvenes.
Raggedy Ann Stories, abridged and adapted from the original, contains 13 short stories about the classic rag doll and her friends. The text is accompanied by the original illustrations, a picture glossary, and questions to aid comprehension. The language has been simplified for high-beginning level English language learners (with vocabulary at the first 1000-word level) and is appropriate for young learners.
Chapter 1: Introduction Chapter 2: Raggedy Ann Learns a Lesson Chapter 4: Raggedy Ann and the Kite Chapter 5: Raggedy Ann and the Painter Chapter 6: Raggedy Ann Saves Fido Chapter 7: Raggedy Ann's Trip on the River Chapter 8: Raggedy Ann and the New Dolls Chapter 9: Raggedy Ann and the Cats Chapter 10: Raggedy Ann and the Gift y otros más....
Keywords: CUENTOS CORTOS; HISTORIETAS CORTOS